Pengembangan Media Jam Bunga Matahari (Jambuhari) pada Materi Membaca dan Menentukan Arah Jarum Jam Kelas 2 SD - Heri Adi Saputra; Fitri Puji Astria (Mataram University, 2026)
This study aims to develop a Sunflower Clock learning media for teaching second-grade elementary school students how to read and determine the direction of clock hands at SDN Timuk Gawah. The development of this learning media was motivated by the lack of student enthusiasm and participation in learning activities due to the limited availability of instructional media. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The study involved 20 second-grade students and one teacher, including 5 students in the small-group trial and 15 students along with one teacher in the large-group trial. Data were collected using questionnaires. The results of the study produced a valid and practical Sunflower Clock learning media. Based on the media expert validation, the learning media achieved a validity score of 80%, while the material expert validation yielded a score of 92.8%. Furthermore, the results of both small-group and large-group trials, involving teacher and student responses, indicated that the Sunflower Clock learning media falls into the practical category, with an average score of 88.4%.